Electrochemical oxidation of aniline using a high-flux CNT filter. (April 2022) - Lin, Shaohua; Zhou, Zhi; Wu, Haixia; Yin, Shenshen; Wang, Yong
Abstract: Carbon nanotube (CNT) membrane electrochemical filtration has been found to provide effective solutions for water contaminant removal. However, bubble elimination, water flux increase, and CNT membrane robustness enhancement still remain great challenges for CNT electrochemical filtration technologies. To improve the performance of the electrochemical CNT filter, a ceramic flat membrane is used as the CNT electrode support. Aniline (AN) is chosen as the target pollutant to investigate the effects of water quality (initial pH, initial AN concentration, and support electrolyte concentration) and running conditions (anode potential and water flux). In addition, the current efficiencies (CE) of the two different modes (single-pass filtration and recirculated filtration) are also estimated. The results showed that the effects of various impact factors on the AN degradation were generally similar in both modes. Overall, the CEs of the sing-pass filtration mode with the stable influent conditions were higher than those of the recirculation filtration mode. Increasing the flux and applied anode potential did increase the AN degradation rate. The maximum water flux density of the high-flux CNT electrochemical filter reached 83.9 mL/(cm 2 ·h), 4.0–16.1 fold of that of a typical CNT electrochemical filter, addressing the defects of bubble formation and CNT fragility of the free-standing BUCKYPAPER membrane in a conventional electrochemical filter. The configuration with a ceramic membrane support greatly improved the practicability of CNT-based electrochemical filtration technology for real wastewater treatment.